CIRCULAR METAPHORIZATION: The metaphor unveiling itself in the universe of the Torah - Cardozo, Guilherme Lima (Revista Húmus, 2015)
The Torah goes through the ages as the most important compendium of Hebrew literature. This work will investigate how the element metaphor appears preponderantly in the reading of the holy text. This element is embodied by the rabbinic parables (mashal), as metaphorical narratives which will attempt to unveil the metaphors inherent in this Book. In this literary context, it is by metaphor that one comes to a divine sense, from the Torah, which is metaphorical from its origin. The conception of this trope in Jewish perspective breaks with the model of metaphor conceived by the Classical Age: here it is a language founding element and can only be unveiled by itself, causing a circular metaphorization, where the literal meaning is not a cause, but an effect of this investigation.